2022
DOI: 10.3390/mi13050674
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Parameter Sensitivity Improvement in ΔE-Effect Magnetic Sensor Based on Mode Localization Effect

Abstract: A mode-localized ΔE-effect magnetic sensor model is established theoretically and numerically. Based on the designed weakly coupled resonators with multi-layer film structure, it is investigated how the ΔE-effect of the magnetostrictive film under the external magnetic field causes the stiffness perturbation of the coupled resonators to induce the mode localization effect. Using the amplitude ratio (AR) as the output in the mode-localized ΔE-effect magnetic sensor can improve the relative sensitivity by three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Both stiffness perturbation and k c tuning were generated by electrostatic tuning. Considering Equation (15), stiffness perturbation could be controlled by V 2 2 + V 2 1 , while k c could be controlled by V 2 2 − V 2 1 . Thus, both parameters could be independently controlled.…”
Section: Mode Localization Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Both stiffness perturbation and k c tuning were generated by electrostatic tuning. Considering Equation (15), stiffness perturbation could be controlled by V 2 2 + V 2 1 , while k c could be controlled by V 2 2 − V 2 1 . Thus, both parameters could be independently controlled.…”
Section: Mode Localization Measurementmentioning
confidence: 99%
“…Mode localization is the phenomenon that detects the small stiffness or mass perturbation applied to weakly coupled resonators [1][2][3][4][5]. Recently, MEMS sensors utilizing mode localization have gained attention for their potential to significantly enhance sensitivity and have been applied to various sensors such accelerometers [6][7][8][9][10], gyroscopes [11], electric current sensors [12], electrometers [13,14] magnetometers [15], and mass sensors [16][17][18]. One major advantage of mode localization sensing is that the change in amplitude ratio is much larger than that in resonant frequency [3].…”
Section: Introductionmentioning
confidence: 99%
“…Morozov et al [26] revealed the principal difference in the characteristics of the mode localization phenomenon for a microelectromechanical accelerometer model. Lyu et al [27] improved the parameter sensitivity of a ∆E-effect magnetic sensor using the mode localization effect. Although there is a great deal of research on the modal localization theory, there is a lack of studies on damage to wind turbine blades based on this theory.…”
Section: Introductionmentioning
confidence: 99%